Macrocycle Conformational Sampling by DFT-D3/COSMO-RS Methodology - Gutten, Ondrej; Bím, Daniel; Řezáč, Jan; Rulíšek, Lubomír (Journal of chemical information and modeling, 2018)
UNLABELLED: To find and calibrate a robust and reliable computational protocol for mapping conformational space of medium-sized molecules, exhaustive conformational sampling has been carried out for a series of seven macrocyclic compounds of varying ring size and one acyclic analogue. While five of them were taken from the MD/LLMOD/force field study by Shelley and co-workers ( Watts , K. S. ; Dalal , P. ; Tebben , A. J. ; Cheney , D. L. ; Shelley , J. C. Macrocycle Conformational Sampling with MacroModel . J. Chem. Inf. MODEL: 2014 , 54 , 2680 - 2696 ), three represent potential macrocyclic inhibitors of human cyclophilin A. The free energy values (GDFT/COSMO-RS) for all of the conformers of each compound were obtained by a composite protocol based on in vacuo quantum mechanics (DFT-D3 method in a large basis set), standard gas-phase thermodynamics, and the COSMO-RS solvation model. The GDFT/COSMO-RS values were used as the reference for evaluating the performance of conformational sampling algorithms: standard and extended MD/LLMOD search (simulated-annealing molecular dynamics with low-lying eigenvector following algorithms, employing the OPLS2005 force field plus GBSA solvation) available in MacroModel and plain molecular dynamics (MD) sampling at high temperature (1000 K) using the semiempirical quantum mechanics (SQM) potential SQM(PM6-D3H4/COSMO) followed by energy minimization of the snapshots. It has been shown that the former protocol (MD/LLMOD) may provide a more complete set of initial structures that ultimately leads to the identification of a greater number of low-energy conformers (as assessed by GDFT/COSMO-RS) than the latter (i.e., plain SQM MD). The CPU time needed to fully evaluate one medium-sized compound (∼100 atoms, typically resulting in several hundred or a few thousand conformers generated and treated quantum-mechanically) is approximately 1,000-100,000 CPU hours on today's computers, which transforms to 1-7 days on a small-sized computer cluster with a few hundred CPUs. Finally, our data sets based on the rigorous quantum-chemical approach allow us to formulate a composite conformational sampling protocol with multiple checkpoints and truncation of redundant structural data that offers superior insights at affordable computational cost.
Keywords: simulace molekulární dynamiky; makrocyklické sloučeniny; Thermodynamics; Crystallography; Molecular Dynamics Simulation; kvantová teorie; algoritmy; kalibrace; Macrocyclic Compounds; molekulární konformace; rychlé screeningové testy; termodynamika; krystalografie; High-Throughput Screening Assays; vysoká teplota; Algorithms; Molecular Conformation; Quantum Theory; Calibration; Hot Temperature